Association between antipsychotics and adverse outcomes in dementia. Issue 4 (27th November 2017) - Bangash, Ayesha; Stubbs, Rebecca; Khan, Farooq; Samnani, Sheliza; Aziz, Humaira; Mitra, Madhumanti
Abstract : Prolonged use of antipsychotics continues to be a controversial subject area, especially in the older adult population due to age‐related changes in pharmacokinetic and pharmacodynamics parameters. Best practice guidelines recommends that they should be used at their lowest dosage for no longer than 6–12 weeks. Here, the authors discuss the prevalence of antipsychotic use to treat the behavioural and psychological symptoms of dementia in the older adult population and the dilemma it poses.